A Study Of Job Stress Level Among Engineering Professionals Working In Manufacturing Sector In India - , Preeti A. Dikshit, Abhishek Y. Dikshit (International Journal of Scientific Research and Management (IJSRM), 2014)
The current research investigated job stress among Engineering professionals aiming to measure the level of job stress and studying the relationship between job stress level of Engineering professionals and a) gender, b) age, c) work experience and d)stress management courses. The research was conducted among 236 Engineering professionals. The results suggest that stress reduction programs and strategies are inevitable due to high job stress levels. The relationship between stress level and gender,work experience, and stress management courses were approved through path analysis. Finally, implications of the study are discussed in terms of discussion and further research.